Diversity and community structure of predators in surjan (polyculture) and lembaran (monoculture) paddy fields - Trisnawati, Dina Wahyu; Nurkomar, Ihsan; Antono, Andri; Puspitasari, Era (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2024)
Predator diversity decreases because of low ecosystem quality in modern agriculture that applies monoculture systems. However, polyculture systems in paddy fields can improve biodiversity, including pests, natural enemies, and microorganisms. Surjan is a local polyculture farming practice that originated in Yogyakarta. This farming practice consists of raised beds for cultivating palawija or horticultural crops and sunken beds for rice cultivation. Surjan farming may have an impact on predatory diversity and abundance, although this has not been studied. To address this issue, research was carried out to investigate the diversity, abundance, and structure of the community of predators in the paddy fields of surjan (polyculture) and lembaran (monoculture). The field experiment was conducted in three pairs, surjan and lembaran, in Panjatan District, Kulon Progo Regency, Yogyakarta Special Region, Indonesia. In each field, five random plots arranged in a cross pattern were used to collect a sample of predators. Several traps, including sweeping, pitfall traps, yellow adhesive traps, and yellow pan traps, were used to determine the abundance and diversity of predators. Results showed that species diversity, abundance, species composition, and biodiversity index in surjan farming were significantly improved compared to lembaran farming. Ceratopogonidae and Formicidae were the most abundant families in both surjan and lembaran farming, although they are more abundant in surjan. It can be concluded from the study that surjan farming could improve ecosystem quality by implementing predators for pest management.